COMPARISON OF MARXIST AND LIBERAL VIEWS ON POWER AND PROPERTY - Arbain, Mayra Putri; Darry, Mohammad (SYNTIFIC, 2025)
Background. Power and property have historically influenced how wealth, resources, and influence are distributed, with significant implications for social stratification and justice. Marxism views property, particularly the means of production, as a primary source of class-based domination, where the capitalist class (the bourgeoisie) exploits the working class (the proletariat), resulting in economic inequality and alienation. In contrast, Liberalism regards private property as a fundamental individual right that promotes freedom, innovation, and market efficiency, although it also acknowledges the risk of excessive power concentration without regulatory oversight. This study explores the contrasting perspectives of Marxism and Liberalism on the concepts of power and property, which are central to understanding political and economic structures in society. Research Methods. The research employs a normative qualitative method through literature review, examining primary and secondary sources, including classical and modern works of political economy. The methodology involves comparative textual analysis of Marxist and Liberal theories, alongside empirical case studies from various national contexts. Findings. Both perspectives offer valuable insights: Marxism highlights systemic inequality driven by capitalism and calls for collective ownership and state intervention. Liberalism emphasizes economic liberty and the protective role of private property, advocating for market-based solutions with minimal state interference. In practice, many countries adopt hybrid systems that integrate elements from both ideologies to balance growth with equity. Conclusion. A flexible, context-sensitive approach is necessary, one that balances economic freedoms with social justice through responsible regulation and equitable property policies.